Synegrizing Humanistic-Digital Andragogy: Enhancing MAster's Students' Engagement in Management Throught Gamification and Visual Thinking - Muhamad Turki; Clara Bonita Dinar Ristanti (Universitas 17 Agustus 1945 Semarang, 2026)
Higher education management at the master's level currently faces urgent challenges, namely learning fatigue and low engagement among professional students, especially in Prior Learning Recognition (RPL) classes. Currently, lecturers still tend to apply conventional learning methods based on static presentations that fail to accommodate andragogical characteristics due to a lack of dynamic interaction. Therefore, this study aims to evaluate the effectiveness of the “Humanistic Digital Andragogy” approach through the integration of gamification (Kahoot) and visual thinking (Whimsical) in the Strategic Human Resource Management course. The researchers used a descriptive qualitative design with thematic analysis and collected data through feedback from students in the Master of Management Program (Semarang and Sorong classes). The results revealed that technology served as a double catalyst: Whimsical visualization effectively reduced the cognitive load of complex strategy material, while competition in Kahoot triggered positive adrenaline (eustress) that increased attention. These findings confirm that the success of technology is highly dependent on the role of lecturers as humanistic facilitators (high-touch). This synergy has been proven to change students' perceptions of HRM from merely administrative to strategic partners, as well as creating learning satisfaction that is relevant to the world of work.